Plan estratégico para la organización Woofme spa y boutique con un horizonte de tiempo 2021 - 2024 - Ceballos Garcia, Laura Isabella; Conu Castillo, Natalia (Universidad Antonio Nariño, 2021)
This work addresses the development of a strategic plan for the Woofme Spa and Boutique organization, with the aim of directing a relevant process that will contribute to its consolidation over the next three years, with competitive dynamics and with value generation for its interest groups, and also presents the results of strategic planning and the challenges it has to take on from the organizational direction, allowing a transformation of the